Effects of environmental salinity on the immune response of the coastal fish Scatophagus argus during bacterial infection. Issue 124 (May 2022) - Lu, Mengying; Su, Maoliang; Liu, Nanxi; Zhang, Junbin
Abstract: The coastal aquaculture is characterized with environmental salinity fluctuation, and the effects of salinity stress on the immunity of cultured fish are needed to be further explored. Scatophagus argus is an important species in the wild fisheries and aquaculture industry, it would be of great value to reveal the impact of salinity change on the immune response in this species. Understanding the effects of salinity stress on immune response can provide valuable insights into salinity management in the aquacultural process. The head kidney, which is an organ unique for teleost fish, functions not only as a central immune organ but also as a crucial role in the stress response during which the secretion of immunoregulatory molecules i.e. cytokines is facilitated. In the present study, Individuals of S. argus acclimated to 3 different salinities [0‰ (FW), 10‰ (BW), and 25‰ (SW)] were injected intraperitoneally with A. hydrophila, and then monitored throughout one week. The effects of environmental salinity on the immune response in S. argus stimulated by A. hydrophila infection were investigated. mRNA expression profiles of cytokine genes IL-1β, IL-6, IL-10 and TNF-α in different salinity groups was quite different. mRNA expression of cytokine genes in BW group and SW group rose more quickly and significantly higher than FW group ( p  < 0.05) at early stages (6–24 hpi) after bacterial injection, and before 96 hpi, the highest value of cytokine expression at each time point was recorded in SW group. Immune parameters such as lysozyme level, complement C3 activity and IgM content in BW and FW groups were lower than SW group at each time point from 24 to 144 hpi after bacterial injection. In addition, leukocyte profiles in the head kidney and blood were also investigated. Although hypoosmotic acclimation could temporarily stimulate monocyte and neutrophil proliferation, it was observed that the number of monocytes, neutrophils and lymphocytes of the head kidney and blood in SW group increased more quickly than BW and FW groups after bacterial infection. Our results indicate that hypoosmotic stress due to the decrease of environmental salinity has suppressive immunoregulatory effects on the immune response of S. argus . Highlights: mRNA expression levels of cytokines in the head kidney of S. argus were impacted by environmental salinity change. Salinity treatments affected immune parameters after bacterial injection. Environmental salinity changes influenced leukocyte profiles in the head kidney and blood of S. argus. Hypoosmotic stress has suppressive immunoregulatory effects on the immune response of S. argus.